Comprehensive Physiology 2010
DOI: 10.1002/cphy.c100017
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Perturbations: Obesity

Abstract: Obesity currently affects about one third of the U.S. population, while another one third is overweight. The importance of obesity for certain conditions such as heart disease and type 2 diabetes is well appreciated. The effects of obesity on the respiratory system have received less attention and are the subject of this chapter. Obesity alters the static mechanic properties of the respiratory system leading to a reduction in the functional residual capacity (FRC) and the expiratory reserve volume (ERV). There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 198 publications
(378 reference statements)
0
7
0
2
Order By: Relevance
“…On the other hand, it has been reported that obesity impairs pulmonary functional capacities and causes airflow obstruction, poor arterial oxygenation, or hypoventilation [42], and it is related to SAHS [49]. All these conditions may benefit from weight loss induced by behavioral interventions [15] or bariatric surgery [27], and also by lifestyle strategies including dietary and physical activity interventions [4].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that obesity impairs pulmonary functional capacities and causes airflow obstruction, poor arterial oxygenation, or hypoventilation [42], and it is related to SAHS [49]. All these conditions may benefit from weight loss induced by behavioral interventions [15] or bariatric surgery [27], and also by lifestyle strategies including dietary and physical activity interventions [4].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, obesity results in physiological lung alterations, such as decreased functional residual capacity and hypoxemia [ 67 ]. In addition, obstructive sleep apnoea hypopnea syndrome (OSAHS) increases adverse outcomes of COVID-19 [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity can cause or exacerbate numerous respiratory conditions including reduction in lung volume, hypoxia, dyspnea, and increased bronchial hyperresponsiveness, and can reduce the effectiveness of inhaled corticosteroids and increase susceptibility to asthma. The inflammatory responses and hypoxemia caused by obesity increase production of ROS, precipitate tissue injury, and disrupt mitochondrial respiratory chain control (44). Sepsis is a state of acute inflammation that affects the lung in an indirect manner.…”
Section: Sources Of Oxidative Stressmentioning
confidence: 99%